2013
DOI: 10.1007/s40520-013-0081-2
|View full text |Cite
|
Sign up to set email alerts
|

Current options to surgical treatment in osteoporotic fractures

Abstract: Treatment of osteoporotic fractures leads to significant challenges for the surgeon, including poor implant fixation related to low bone quality and compromised capacity of fracture healing. This article reviews the osteosynthesis and arthroplasty results in the surgical treatment of proximal femur, proximal humerus and wrist fractures to define the current options to decrease failure in fragility fracture management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Even though periprosthetic fractures are not included in the current definition of AFs, available data indicate that there may be similar underlying pathology. Therefore, treatment includes both surgical than pharmacological therapy (20). In unstable acetabular components, with uncontained cavitary defect and severe bone loss revision surgery is mandatory, but there might be likely an important role of anabolic drugs in promoting fracture healing.…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…Even though periprosthetic fractures are not included in the current definition of AFs, available data indicate that there may be similar underlying pathology. Therefore, treatment includes both surgical than pharmacological therapy (20). In unstable acetabular components, with uncontained cavitary defect and severe bone loss revision surgery is mandatory, but there might be likely an important role of anabolic drugs in promoting fracture healing.…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…Zhen reported 100% of union after plating and vascularized fibular osteo-septocutaneous flap graft for complex tibial shaft complex fractures; however, 10 out 38 experimented donor-site morbidities [17]. Moreover, bone grafting represents an additional option in all the osteoporosis related and so-called fragility fractures [10]. Limitations of ABG extensive use are the limited availability, graft dimension and donor site morbidity (i.e., iliac crest or fibula) [18].…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological interventions that could modulate the healing process positively have been recently merged to the treatment algorithm, where systemic anti-osteoporosis drugs are considered the additional contributing factor [8]. The role of systemic drug therapies in long bones fracture healing remains limited, although the use several anabolic agents has reported positive results in selected shaft fractures types, such as atypical femoral fractures, periprosthetic femoral fractures and recalcitrant non-unions [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Given that advanced imaging modalities have not been shown to improve interobserver agreement, we compared the three classification systems using only x-rays. Nevertheless, CT scans and 3D reconstruction play a crucial role Marongiu et al J Orthop Traumatol (2020) 21:4 for valuable comprehension of the fracture and to plan a surgical approach in more complex cases [33]. Torrens et al found that addition of 3D imaging of proximal humeral fractures significantly increased the number of surgical decisions when compared with radiographs alone or together with CT [34].…”
Section: Discussionmentioning
confidence: 99%